MO066GASDERMIND MUTATION IS PROTECTIVE AGAINST RENAL ISCHEMIA REPERFUSION INJURY. (6th June 2020) - Rogers, Natasha; Li, Jennifer; Alexander, Stephen
Abstract: Background and Aims: Ischemia reperfusion injury (IRI) is an important contributor to acute kidney injury (AKI) and manifests as delayed graft function following kidney transplantation. Limiting the damage of IRI has implications on graft outcomes and has driven further exploration of the underlying pathophysiology. We hypothesize that pyroptosis, a pro-inflammatory form of cell death, has an important role in IRI and AKI. The pyroptosis pathway converges to the cleavage and release of N-terminal of the Gasdermin-D protein, leading to pore formation in the cell membrane and cell death. We examined the effects of Gasdermin-D mutation on inflammation in acute kidney injury. Method: Male C57BL/6 mice were exposed to ethyl- N -nitrosourea mutagenesis, leading to a loss-of-function, single nucleotide polymorphism (isoleucine to asparagine mutation, I105N) in the Gasdermin-D gene. Age- and gender-matched littermate control wild-type, heterozygous and homozygous Gasdermin-D I105N mice were subjected to bilateral renal IRI (36°C, 22mins) and sacrificed 24-hours post-reperfusion for analysis of renal function, histology and biomolecular phenotyping. To delineate if the GasderminD mutation in renal parenchymal or hematopoietic cells were key drivers of IRI, we generated chimeric mice with whole body irradiation and infusion of syngeneic donor bone marrow. Following 8 weeks of engraftment, bilateral renal IRI was performed with analysis at 24 h reperfusion. Results: Homozygote and heterozygote Gasdermin-D I105N mice were protected from renal IRI in a gene dose-dependent manner when compared to wild-type, with lower mean serum creatinine (15.7, 48.1 and 85.5µmol/L respectively, p<0.001), less histological tubular injury and cell death (1.8, 3.6 and 5.1 TUNEL+ cells/hpf, p<0.01) and significantly decreased expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, RANTES). Homozygote GasderminD I105N chimeric mice (reconstituted with wild-type donor bone marrow) were more susceptible to IRI, and serum creatinine was similar to that of wild-type chimeric control mice, indicating that hematopoietic cells rather than parenchymal cells, are likely predominant drivers of injury. Similarly, adoptive transfer of CpG-activated CD11c+ dendritic cells into homozygous Gasdermin-D I105N mice augmented renal injury compared to GpC-treated cells. Conclusion: GasderminD I105N mice were protected from IRI and demonstrates the importance of the pyroptosis pathway on acute kidney injury. Manipulation of GasderminD is potentially an attractive target to mitigate inflammation and cellular death following injury.